New research progress in Ti2AlCN MAX phases and their reinforced magnesium composites - Yu, Wenbo (Cambridge Scholars Publishing, 2022)
Providing an up-to-date discussion of advanced ternary MAX ceramics, including their synthesis, mechanical and electrical transport properties, oxidation behavior and their reinforcement in Mg composites, this book introduces students and engineers to the key research topics in the field. By explaining structural materials in a clear and detailed way, it explores Ti2AlCxNy MAX ceramics, from their fundamental investigation to their industrial application. This book also details the synthesis of Ti2AlCxNy, the solid solution and vacancy effects on the mechanical and electrical transport propert.